Generalization properties for certain analytic functions - Shigeyoshi Owa (International Journal of Mathematics and Mathematical Sciences)
The object ofthe present paper is to give some generalizations of results for certain analytic functions which were proved by Saitoh (Math. Japon. 35 (1990), 1073-1076). Our results contain some corollaries as the special cases.